Low generation PAMAM-based nanomicelles as ROS-responsive gene vectors with enhanced transfection efficacy and reduced cytotoxicity in vitro. (28th March 2017) - Xu, Chen-Tao; Chen, Guang; Nie, Xuan; Wang, Long-Hai; Ding, Sheng-Gang; You, Ye-Zi
Abstract : ROS-responsive cationic nanomicelles formed from amphiphilic PPS–SS–PAMAMG2.0 conjugates exhibit high transfection efficacy and low cytotoxicity. Abstract : Poly(amidoamine)s (PAMAMs) of high-generations ( G > 5) exhibit high efficacy in gene transfection, but their high cost and severe cytotoxicity limit their use in biomedicine. In contrast, PAMAMs of low-generations ( G < 3) are less toxic and easy to synthesize, but exhibit low transfection efficacy. In this report, we design a novel amphiphilic dendrimer by conjugating reactive oxygen species (ROS)-responsive poly(propylenesulfide) (PPS) to a low generation PAMAM dendrimer ( G = 2, M w = 3500 Da) via disulfide bonds. This amphiphilic conjugate can self-assemble into stable nanomicelles. The results show that the obtained nanomicelles have a high zeta potential, which can condense DNA tightly. Moreover, the DNA/nanomicelle polyplexes can be fully dissociated by intracellular ROS and easily release the entrapped DNA. As gene vectors, the nanomicelles exhibited high transfection efficacy and fairly low cytotoxicity in vitro .